1998
DOI: 10.1002/j.1551-8833.1998.tb08402.x
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in As analysis and speciation

Abstract: A modified field technique can quantify particulate As, soluble As(III), and soluble As(V) in drinking water. Several problems with commonly used techniques that analyze for arsenic are reported, and solutions are proposed. Analytical techniques can accurately detect <0.5 μg/L total arsenic if certain conditions are met: iron, nitrate, and other interferences are overcome in hydride generation techniques, poor recoveries are overcome in graphite furnace atomic adsorption techniques, and chloride interferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 13 publications
(21 reference statements)
1
55
0
Order By: Relevance
“…2 it is also evident that under the experimental conditions, at the Fe(II) concentration of 7.5 mg/L, the % increment in the eluent As(T) concentration is around 10 %. This observation agrees well with the observation of Edwards et al [5]. In that experiment, the acidified solution of As(III) and As(V) containing 5.6 mg/L Fe(III) was passed through the resin column filled with acetate form resin.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…2 it is also evident that under the experimental conditions, at the Fe(II) concentration of 7.5 mg/L, the % increment in the eluent As(T) concentration is around 10 %. This observation agrees well with the observation of Edwards et al [5]. In that experiment, the acidified solution of As(III) and As(V) containing 5.6 mg/L Fe(III) was passed through the resin column filled with acetate form resin.…”
Section: Resultssupporting
confidence: 89%
“…It is also evident that due to the exchange of H2AsO4 -by the acetate ion, the eluent pH increases due to the changes in resin surface and environment. To maintain the eluent pH value below 5, the inlet sample was acidified to 0.02 N H2SO4 [5]. The change of pH may alter the charge of the available arsenic species as shown in Tab.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, agrochemicals containing high levels of NO 3 and PO 4 in waters have been shown to enhance/suppress MA V levels from the SPE methodology utilised in this study by as much as 13 -21 % (Watts et al [THIS ISSUE]). Previous studies on the levels of arsenic in waters have mainly reported only inorganic species (As III and As V ), in which As V was deduced from the subtraction of As III from the total arsenic level (Sigrist and Beldoménico 2004;Edwards et al 1998). This subtraction method does not account for organoarsenicals and may provide apparently elevated concentrations for As V .…”
Section: Discussionmentioning
confidence: 99%